Does Migration Foster Exports? Evidence from Africa - Ehrhart, Hélène (The World Bank, 2014)
This paper aims at assessing the impact of migration on export performance and more particularly the effect of African migrants on African trade. Relying on a new data set on international bilateral migration recently released by the World Bank spanning from 1980 to 2010, the authors estimate a gravity model that deals satisfactorily with endogeneity. The results first indicate that the pro-trade effect of migration is higher for African countries, a finding that can be partly explained by the substitution between migrants and institutions (the existence of migrant networks compensating for weak contract enforcement, for instance). This positive association is particularly important for the exports of differentiated products, suggesting that migrants also play an important role in reducing information costs. Moreover, focusing on intra-African trade, the pro-trade effect of African migrants is larger when migrants are established in a more geographically and ethnically distant country. All these findings highlight the ability of African migrants to help overcome some of the main barriers to African trade: the weakness of institutions, information costs, cultural differences, and lack of trust